(untitled) (Ukrainian Journal of Ophthalmology, 2023)
Introduction. Basal cell carcinoma is the most common tumour of the eyelids and periocular region throughout the world. BCC represents 90 % of malignant tumours of the eyelids, predominantly in the male population. The incidence is higher in age over 60. Over 50% of BCC of the periocular region initially occur on the lower lid and inner angle. Research objectives. Literature review of the epidemiology, aetiopathogenesis, clinical attributes, diagnostics, treatment histopathology, recurrence, prognostic factors, and management of BCC. Core of work. Standardised incidence of diagnosis C44 in the period 1997–2012 in Slovakia ranged from 35.05 to 73.9 cases per 100,000 inhabitants. The histopathological examination is essential. The first consideration for treatment of periocular BCC is radical surgical excision using Mohs micrographic technique. We can consider the apoptotic index, the expression of Bcl-2, as an unexplained prognostic factor of BCC recurrence. Conclusion. Increased attention must be given to periocular malignant tumours. Functional and aesthetic outcome in patients is important after clear excisions and reconstruction should be carefully considered. Radical exenteration is considered in the case of orbital invasion of high-risk aggressive BCC.